Effects Of Lean Manufacturing Practices On Operational Performance - Edy Suroso; Allicia Deana Santosa (Journal of Research in Social Science and Humanities, 2024)
Lean manufacturing is a concept of process improvement in production management which focuses on waste elimination. This paper explores relationships between lean manufacturing practices and operational performance. Using data collected from 55 manufacturing companies in Tasikmalaya city. Lean manufacturing were measured by five dimensions: production flow management, customer focus, process management, workforce management, and supplier management. Operational performance comprises four dimensions: cost, quality, lead-time, and flexibility. The findings are that all dimensions of lean manufacturing are significantly related to on operational performance. Production flow management has a higher level of significance in large enterprises compared with SMEs, whereas for customer focus there is a higher level of significance in SMEs compared with large enterprises. Process management, supplier management and workforce management have much lower level of significance for both SMEs and large enterprises.